Annual Plan 1969-70 Government of Goa, Daman and Diu - Planning Commission (Planning Commission, 1969)
The important schemes to be taken up in the year 1969-70 under the Forest Programme include extensive introduction of cashew plantation and other forest plantations. Communications and Buildings will also to be taken up as plan schemes during this year. A total expenditure of Rs.28.58 lakhs is proposed under this head.
Government of Goa, Daman and Diu, Planning Department